2010
DOI: 10.1007/s10689-010-9365-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective COX-2 inhibition affects fatty acids, but not COX mRNA expression in patients with FAP

Abstract: Familial adenomatous polyposis (FAP) provides a model for sporadic colorectal cancer development. Cyclooxygenase (COX) inhibition may ameliorate polyp development, but rofecoxib was withdrawn due to cardiovascular side effects. Although this selective COX-2 inhibitor, like diet, may alter the fatty acid and eicosanoid pattern, data on the potential alteration in tissues after use, are scarce. The aims were to study if rofecoxib might influence the fatty acid distribution in serum phospholipids and duodenal les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…Previous reports support the present finding that PGE2 content is not changed upon decreasing COX-2 expression (31)(32)(33)(34)(35). A number of authors have demonstrated that in the Vhl ∆IE /Apc min / + intestinal tumor model, the production of PGE2 is not dependent on the levels of COX-2, since despite the blockage of COX-2 activity by nimesulide, the PGE2 content remained elevated, suggesting that the high PGE2 levels observed were due to an increase in mPGES1 expression (31,32).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Previous reports support the present finding that PGE2 content is not changed upon decreasing COX-2 expression (31)(32)(33)(34)(35). A number of authors have demonstrated that in the Vhl ∆IE /Apc min / + intestinal tumor model, the production of PGE2 is not dependent on the levels of COX-2, since despite the blockage of COX-2 activity by nimesulide, the PGE2 content remained elevated, suggesting that the high PGE2 levels observed were due to an increase in mPGES1 expression (31,32).…”
supporting
confidence: 92%
“…In addition, mPGES1 has been observed to be increased in CRC tumor tissues and to correlate with a worse prognosis (34). Almendingen et al (35) reported that treatment with rofecoxib, a COX-2 selective inhibitor, did not affect the PGE2 levels in plasma of patients with familial adenomatous polyposis. Altogether, those findings offer an explanation for the present results.…”
mentioning
confidence: 99%
“…Colectomized familial adenomatous polyposis patients had a deviant fatty acid profile with high levels of arachidonic acid and docosahexaenoic acid and low levels of linoleic acid and alpha-linolenic acid in serum phospholipids, which is in accordance with studies in patients with other types of cancers [5, 1013]. In a previous familial adenomatous polyposis study [14], comparable treatment effects of a cyclooxygenase-2 inhibitor were observed on the fatty acid composition in serum phospholipids and duodenal lesions, presumably and most importantly the nonbeneficial effects involving essential fatty acids. …”
Section: Introductionsupporting
confidence: 86%
“…This result can be explained by the allosteric regulation of COXs by FAs. COXs are inhibited by celecoxib and this can help reduce the AA‐to‐EPA ratio (Almendingen et al, , ; Dong et al, ). Furthermore, upregulated expression of COX‐2 was observed in several metabolic disorders including obesity and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by the allosteric regulation of COXs by FAs. COXs are inhibited by celecoxib and this can help reduce the AA-to-EPA ratio (Almendingen et al, 2007(Almendingen et al, , 2010Dong et al, 2016).…”
Section: Studied Parameters In Interventional Groupsmentioning
confidence: 99%